Being Active in Working Life at Age 60, 66, and 72 - Bjuhr, Marie; Engström, Maria; Welmer, Anna-Karin; Elmståhl, Sölve; Sjölund, Britt-Marie (Nordic Journal of Working Life Studies, 2024)
This study examines associations between participation in working life and sociodemographic, health, and work environment factors among people aged 60, 66, and 72 years. The agestratified logistic regression analysis used data from 2001–2003 (T1) and 2013–2015 (T2) derived from The Swedish National Study on Ageing and Care. Further, interaction variables with time*independent variables explored differences in those associations over time. We found positive associations between being active in working life and male gender (age 66 and 72), higher education (all age groups), higher professional level (age 60 and 66), better health (age 60 and 66), less negative work experiences (mainly age 60), light level of physical activity at work (age 60 and 66), higher work satisfaction (age 60 and 66), and time: that is,T2 vs.T1 (all age groups). Not only health status but also work environment factors were shown to play a significant role in being active in working life at older ages. Our findings verify that authorities need to develop reforms aiming at keeping older people active in working life from a heterogeneous perspective.